2003
DOI: 10.1038/ng1084
|View full text |Cite
|
Sign up to set email alerts
|

Extensive allelic variation and ultrashort telomeres in senescent human cells

Abstract: By imposing a limit on the proliferative lifespan of most somatic cells, telomere erosion represents an innate mechanism for tumor suppression and may contribute to age-related disease. A detailed understanding of the pathways that link shortened telomeres to replicative senescence has been severely hindered by the inability of current methods to analyze telomere dynamics in detail. Here we describe single telomere length analysis (STELA), a PCR-based approach that accurately measures the full spectrum of telo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

27
487
0
3

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 478 publications
(517 citation statements)
references
References 28 publications
27
487
0
3
Order By: Relevance
“…4,6-Diamidino-2-phenylindole staining of squash preparations detected the presence of cells (57.4 ± 8.7%, mean ± s.d., Po0.001 compared with control mice) with aberrant nuclei in tumor tissue from 70124-treated mice (Figure 8f). Furthermore, tumor cells from mice treated with the inhibitor showed a threefold reduction (Po0.0001) in telomeric signal intensity for individual nuclei compared with untreated mice, indicating a decrease in telomere length (Figure 8g), which is known to trigger cell cycle arrest and replicative senescence in human cells (Baird et al, 2003). Additionally, 46.1±11.4% (mean±s.d.)…”
Section: Treatment With 70124 Induces Tumor Cell Senescence In Mice Xmentioning
confidence: 97%
“…4,6-Diamidino-2-phenylindole staining of squash preparations detected the presence of cells (57.4 ± 8.7%, mean ± s.d., Po0.001 compared with control mice) with aberrant nuclei in tumor tissue from 70124-treated mice (Figure 8f). Furthermore, tumor cells from mice treated with the inhibitor showed a threefold reduction (Po0.0001) in telomeric signal intensity for individual nuclei compared with untreated mice, indicating a decrease in telomere length (Figure 8g), which is known to trigger cell cycle arrest and replicative senescence in human cells (Baird et al, 2003). Additionally, 46.1±11.4% (mean±s.d.)…”
Section: Treatment With 70124 Induces Tumor Cell Senescence In Mice Xmentioning
confidence: 97%
“…A more detailed analysis of telomere lengths was carried out using single telomere length analysis (STELA) (Baird et al, 2003) (Figure 5c, supplementary Figure). Analysis of the XpYp telomere confirmed that hTERT þ cells had longer telomeres than hTERTÀ cells.…”
Section: Metal-induced Genomic Instabilitymentioning
confidence: 99%
“…STELA DNA extractions and STELA reactions were carried out as previously described (Baird et al, 2003), with the following adaptations: The Taq/Pwo ratio was adjusted from 25:1 to 10:1 and we cycled the reactions with an MJ PTC-225 thermocycler (MJ research) under the following conditions: 22 cycles of 941C for 15 s, 651C for 30 s and 681C for 10 min. To ensure specificity of telomeric bands only those that hybridized to both the telomere-adjacent and telomere-repeat containing probe were analysed.…”
Section: Cell-cycle Analysismentioning
confidence: 99%
“…In human beings, telomere shortening contributes to mortality in many age-related diseases (34). Notably, it is reported that some alleles show almost complete loss of TTAGGG repeats in senescence (35). Thus, telomere shortening has been suggested to be a 'molecular clock' of the aging process.…”
Section: The Role Of Reactive Oxygen Species In Agingmentioning
confidence: 99%